Gene expression alterations in the medial prefrontal cortex and blood cells in a mouse model of depression during menopause - Miyata, Shigeo (Heliyon, 2016)
AIMS: The prevalence of major depressive disorder (MDD) is higher in women than in men, and this may be due to the decline in estrogen levels that occurs during the menopausal transition. We studied the biological alterations in the medial prefrontal cortex (mPFC), which is a region that is highly implicated in the neurobiology of MDD, and the blood cells (BCs) of ovariectomized (OVX) mice subjected to chronic mild stress (CMS), which represents a mouse model of depression during menopause. MAIN METHODS: The mPFC and the BCs were obtained from the same individuals. Gene expression levels were analyzed by microarray. The data were used for the Ingenuity Pathway Analysis and the Gene Ontology analysis. KEY FINDINGS: The gene expression alterations (GEAs) induced by OVX were mainly associated with ribosomal and mitochondrial functions in both the mPFC and the BCs. Rapamycin-insensitive companion of mTOR (RICTOR) was identified as a possible upstream regulator of the OVX-induced GEAs in both tissues. The CMS-induced GEAs were associated with retinoic acid receptor signaling, inflammatory cytokines and post-synaptic density in the mPFC, but not in the BCs. SIGNIFICANCE: OVX and CMS independently affect biological pathways in the mPFC, which is involved in the development of the depression-like phenotype. Because a subset of the OVX-induced GEAs in the mPFC also occurred in the BCs, the GEAs in the BCs might be a useful probe to predict biological pathways in the corresponding brain tissue under specific conditions such as OVX in females.